The Effect of Audit Term, Company Size, and Audit Delay on Audit Quality in Companies - Meliatikasari, Meliatikasari; Saputra, Agung Joni (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
The purpose of this study is to investigate mining companies listed on the Indonesia Stock Exchange that are engaged in the coal subsector and to identify the factors that influence audit quality, audit delay, company size, and audit duration. This research collects quantitative data from 18 IDX enterprises using a purposive sampling technique. Thirteen of these businesses submitted 65 financial reports that were considered complete for the years 2019–2023. We used SPSS 27 to extract and analyze the data from the documents. Audit tenure and company size do not significantly affect audit quality (p > 0.05 and p > 0.935, respectively), but audit delay does have a substantial influence (p < 0.05), as can be shown from the data. The simultaneous impact of audit tenure, firm size, and audit delay on audit quality is statistically significant (p = 0.003, < 0.05). Only coal subsector mining companies registered on the IDX will be included in this study. The key takeaway from this research is an improved understanding of the relationships between audit quality, audit delay, company size, and audit duration